(untitled) (Journal of Pharmaceutical Negative Results, 2022)
This study presents a comprehensive analysis of the influence of socioeconomic and lifestyle factors on oral health, using the MICMAC technique to classify these factors into key, determinant, autonomous, and result factors. The research identifies a complex interaction of factors, in which socioeconomic elements such as income and educational level emerge as key influencing factors due to their direct impact on access to dental care and oral hygiene practices. Lifestyle factors, including dietary habits, tobacco use, and alcohol consumption, have been found to have a direct influence on the incidence of oral diseases. The findings emphasize the need for multifaceted approaches to promote oral health, addressing socioeconomic, lifestyle, and cultural aspects. This research provides a valuable foundation for making informed decisions and designing effective oral health strategies aimed at improving quality of life and oral health equity among diverse populations.